2021
DOI: 10.3390/genes12020129
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA Methylation Landscape in Skin Fibroblasts from African Americans with Systemic Sclerosis

Abstract: The etiology and reasons underlying the ethnic disparities in systemic sclerosis (SSc) remain unknown. African Americans are disproportionally affected by SSc and yet are underrepresented in research. The aim of this study was to comprehensively investigate the association of DNA methylation levels with SSc in dermal fibroblasts from patients of African ancestry. Reduced representation bisulfite sequencing (RRBS) was performed on primary dermal fibroblasts from 15 SSc patients and 15 controls of African ancest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…We found most of the differential methylation in intergenic regions and on introns (Figure 2C,D,F,G). Although differential methylation of noncoding regions has been reported, 16–24 little is known about its biological functions. Initially, we used HOMER to determine motif enrichment in hypo‐ and hyper‐DMSs, and found motifs supporting our model and phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found most of the differential methylation in intergenic regions and on introns (Figure 2C,D,F,G). Although differential methylation of noncoding regions has been reported, 16–24 little is known about its biological functions. Initially, we used HOMER to determine motif enrichment in hypo‐ and hyper‐DMSs, and found motifs supporting our model and phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] To date, most studies have focused on probing the alterations in DNA methylation near genes and promoters, which are easier to mechanistically link to changes in gene expression. Nonetheless, there is a growing body of literature from different animal models, tissues, and cell types reporting on prevailing differential methylation in intergenic regions, introns, and other noncoding DNA regions, [16][17][18][19][20][21][22][23][24] following the contextual and environmental stimulus. These areas in the genome may harbor cis-and trans-regulatory elements of transcription, also known as enhancers.…”
Section: Introductionmentioning
confidence: 99%
“…Coit et al [ 70 ] identified a total of 105 and 144 differentially methylated sites and genes unique for either juvenile SSc (JSSc) and localized SSc including FGFR2, STAT3, NF-κB, IL-15, and NOTCH3 pathways. Baker Frost et al [ 71 ] intended to investigate the association of DNA methylation levels in dermal fibroblasts obtained from patients of African ancestry and found widespread reduced DNA methylation of DLX5 and TMEM140. Rezaei et al [ 72 ] suggested that hypomethylation of IRF7 promotor might play a role in SSc pathogenesis via promoting the IRF7 expression in PBMCs of patients with SSc.…”
Section: The Roles Of Genetics Environmental Risk Factors Stochastic Processes and Epigenetics In The Pathogenesis Of Patients With Systementioning
confidence: 99%
“…Variation in DNA methylation across ancestral populations is contributed to by genetic ancestry and environmental factors [ 20 ]. Despite the increased disease burden in African Americans and variation in DNA methylation across populations, only two genome-wide differential DNA methylation analyses have been conducted in peripheral blood and skin fibroblasts from SSc patients of African descent [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%